Business transactions and ownership ties between firms - László Lőrincz; Sándor Juhász; Rebeka O. Szabó (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
In this study we investigate the creation and persistence of interfirm ties in a large-scale business transaction network. Transaction ties, firms buying or selling products or services can be the outcome of pure business motivations, but the social connections of owners or the geographical location of companies may also influence their development. We build the transaction and the ownership networks of firms in Hungary for 2016 and 2017 from two administrative datasets and identify multi-layer network motifs to predict the creation and persistence of business transactions. We show that direct or indirect relationships in this two-layered network contribute to both the creation and persistence of business transaction ties. We find a positive, but smaller impact of geographic proximity and industrial similarity of firms. For our estimations, we utilize loglinear models and emphasize their efficiency in predicting links in such large networks. We contribute to the literature by illustrating business connection patterns in a nationwide multilayer interfirm network.
Keywords: L14; 330; transaction network; ownership network; multilayer network; network motifs; tie creation; tie persistence